Cinéma-monde : decentred perspectives on global filmmaking in French - Gott, Michael; Schilt, Thibaut (Edinburgh University Press, 2018)
With contributions from an international range of specialists, and with considerations of works by contemporary directors like Rachid Bouchareb, Abderrahmane Sissako and Rithy Panh, Cinema-monde explores the porous borders around francophone spaces and the ways in which languages and identities travel' in contemporary cinema.